(untitled) (المجلة الدولية للعلوم التربوية والآداب, 2025)
This study aimed to explore the relationship between health services and social adaptation among patients at Al Noor Specialized Hospital in Makkah. It also sought to examine the role of social workers in helping patients achieve better adaptation, as well as to identify the awareness and educational programs provided for individuals with chronic illnesses. The study adopted the social survey method and was conducted on a purposive non-probability sample consisting of 101 patients receiving services at the hospital. The main data collection tool used was a questionnaire, and data were analyzed using the SPSS statistical software. The findings revealed several important results. Most notably, participants agreed that the hospital provides health services that are linked to social adaptation, with a mean score of 2.35. One of the most significant services identified was the hospital’s attention to patient feedback and inquiries. The study also showed agreement among participants regarding the active role of social workers in enhancing social adaptation among patients, with a mean score of 2.57. Among the key roles identified was the ability of social workers to reduce feelings of fear, pain, and anxiety experienced by patients. Furthermore, participants agreed on the presence of awareness and educational programs for individuals suffering from chronic illnesses, with a mean score of 2.52. One of the main aspects highlighted was the hospital’s efforts in providing information about the complications of chronic diseases. The study recommended the need to train social workers and hospital staff to recognize signs of poor social adaptation among patients and to develop appropriate guidance programs to address these challenges.